GPR30 mediates estrone, estriol, and estradiol to suppress gonadotropin-releasing hormone-induced luteinizing hormone secretion in the anterior pituitary of heifers - OTSUKA, Midori; KADOKAWA, Hiroya (Journal of Reproduction and Development, 2017)
Recent studies demonstrated that G-protein-coupled receptor 30 (GPR30) on the plasma membrane of gonadotroph cells mediates picomolar, but not nanomolar, levels of estradiol (E2) to rapidly suppress gonadotropin-releasing hormone (GnRH)-induced luteinizing hormone (LH) secretion in the anterior pituitary (AP). While estrone (E1) and estriol (E3) are considered “weak” estrogens that exert suppressive effects through estrogen receptors α and β, it is conceivable that they also strongly suppress GnRH-induced LH secretion via GPR30. Both E1 and E3 are likely present within the blood at picomolar or nanomolar concentrations, indicating that such concentrations are sufficient to suppress GnRH-induced LH secretion. To evaluate this possibility, bovine AP cells were cultured under steroid-free conditions and then incubated with various concentrations (0.01 pM to 10 nM) of E2, E1, or E3, prior to stimulation with GnRH. Notably, GnRH-induced LH secretion from AP cells was inhibited by 1–100 pM E2, 1–10 pM E1, and 1–100 pM E3. GnRH-induced LH secretion from AP cells was not inhibited by lower (0.01–0.1 pM) or higher (1–10 nM) concentrations of E2, E1, and E3. These suppressive effects were inhibited by pre-treatment of AP cells with the GPR30 antagonist G36, but not with the estrogen receptor alpha antagonist. Treatment with E1 or E3 also yielded decreased cytoplasmic cAMP levels in cultured AP cells pre-treated with dopamine and phosphodiesterase inhibitors. Therefore, these results suggest that GPR30 mediates the suppressive effects of E1, E3, and E2 on GnRH-induced LH secretion from bovine AP.